SOSIALISASI PENCEGAHAN NARKOBA PADA REMAJA DI SMA IT ABDURAB PEKANBARU - Adha, Afifah Cahayani; Indra, Hamdi; Iswanti, Dewi Nur; Marliana (LPPM Universitas Awal Bros, 2023)
The aim of the activity to socialize the dangers of drug abuse in Senior High Schools (SMA) IT Abdurab Pekanbaru so that participants can understand the impact caused by drug use, both physical, psychological and socio-economic impacts. Socialization activities use participatory methods, lectures and discussions. The socialization activity was carried out on October 31 2023 with the number of participants taking part in the socialization activity consisting of 40 students and 15 teachers located in the hall of SMA IT Abdurab Pekanbaru. For this reason, through socialization activities on the dangers of drug abuse, it is possible to increase the understanding of SMA IT Abdurab Pekanbaru students regarding the types of narcotics, the impact of drug abuse from physical, psychological, educational, social and economic aspects as well as ways to prevent and overcome drug abuse among children and teenager. For this reason, this socialization activity can strengthen the younger generation as the nation's next generation, especially students at SMA IT Abdurab. Pekanbaru from the dangers of drug abuse.